Photoclinic - Kokcam, Ibrakim (Academy of Medical Sciences of I.R. Iran, 2008)
[Abstract Not Available]
Keywords: alcian blue; collagen fiber; corticosteroid; eosin; hematoxylin; isotretinoin; acne vulgaris; adult; anamnesis; article; back; case report; cell infiltration; dermatomycosis; differential diagnosis; drug treatment failure; erythema; female; fibroblast; follow up; histopathology; human; lymphocytic infiltration; mast cell; mucinosis; papule; patient referral; plaquelike cutaneous mucinosis; skin biopsy; skin defect; treatment refusal